Normocalcemic Primary Hyperparathyroidism: Need for a Standardized Clinical Approach - Zavatta, Guido (Endocrinol Metab (Seoul), 2021)
Since normocalcemic primary hyperparathyroidism (NHPT) was first defined at the Third International Workshop on the Management of Asymptomatic Primary Hyperparathyroidism in 2008, many papers have been published describing its prevalence and possible complications. Guidelines for the management of this condition are still lacking, and making the diagnosis requires fulfillment of strict criteria. Recent studies have shown that intermittent oscillations of serum calcium just below and slightly above the normal limits are very frequent, therefore challenging the assumption that serum calcium must be consistently normal to make the diagnosis. There is debate if these variations in serum calcium outside the normal range should be included under the rubric of NHPT or, rather, a milder form of classical primary hyperparathyroidism. Innovative approaches to define NHPT have been proposed that still need to be validated in prospective studies. Non-classical complications, especially cardiovascular complications, have been associated with NHPT, indicating that hyperparathyroidism may be a cardiovascular risk factor. New associations between parathyroid hormone (PTH) and several other comorbidities have also been reported from observational studies, suggesting that excessive PTH secretion might cause tissue dysfunction independent of serum calcium. Heterogeneous studies using different definitions of NHPT, however, make it difficult to draw definitive conclusions regarding the role of PTH excess when complications other than osteoporosis or kidney stones are described. This review will focus on clinical aspects and suggest an approach to NHPT.